Optimal MAP Parameters Estimation in STAPLE using Local Intensity Similarity Information - Gorthi, Subrahmanyam (IEEE J Biomed Health Inform, 2015)
In recent years, fusing segmentation results obtained based on multiple template images has become a standard practice in many medical imaging applications; such multiple-templates-based methods are found to provide more reliable and accurate segmentations than the single-template-based methods. In this paper, we present a new approach for learning prior knowledge about the performance parameters of template images using the local intensity similarity information; we also propose a methodology to incorporate that prior knowledge through the estimation of the optimal MAP parameters. The proposed method is evaluated in the context of segmentation of structures in the brain Magnetic Resonance (MR) images by comparing our results with some of the state-of-the-art segmentation methods. These experiments have clearly demonstrated the advantages of learning and incorporating prior knowledge about the performance parameters using the proposed method.